Secondary school heads' competencies : basic for the development of a capability building program - Baptista, Virgilio Ericson G. (Laoag City : [s.n.], 2018)
The competencies of secondary schools heads and their functions were studied for the formulation of a Capability Building Program based on the perceived least performed competencies and functions that are considered very challenging. The methodology used was research and development (R&D). Data were gathered using a survey questionnaire adapted from the competency framework created by Southeast Asian Ministers of Education Organization-Innovation and Technology (SEAMO-INNOTEC). There were 38 school heads, 24 ministers supervisors and 104 teachers who were involved in the study.
Bibliography: pages 165-171.
CHED-La Union
Keywords: Schools -- Administration